Waste heritage - Baird, Irene (Canadian literature collection., 2007)
"A new critical edition of the best-selling Canadian novel of the 1930s, Irene Baird's Waste Heritage is a groundbreaking work of Canadian fiction based on the dramatic and violent labour disputes that took place in British Columbia in 1938"--Résumé de l'éditeur.